Interdisciplinary Approaches to Assessing the Health of People Living in Environmentally Adverse Conditions - Yerbol BEKMUKHAMBETOV; Arstan MAMYRBAYEV; Timur JARKENOV; Talgar ABILOV; Gulnar SULTANOVA; Gulnar ISAEVA; Mukhtar ZHAILYBAYEV; Raisa URAZ (Tehran University of Medical Sciences, 2019)
Background: The health status of the population of different ages was examined. Since children are very vulnerable to environmental factors, our goal was to examine their health status and compare them with those of the older population. Also one of the important tasks of our study was the installation of carcinogenic and non-carcinogenic risks for children and adults of different sexes. Methods: During our research, we calculated the air pollution index, investigated the incidence statistics of the population, and calculated the lifetime average daily dose (LADD). We investigated the content of sulfur dioxide, hydrogen sulfide, nitrogen oxide, ammonium and hydrogen carbonates and compared it with safe level of exposure. Results: In Aktobe, the Republic of Kazakhstan the external environment is polluted with boron and chromium, and in Aktau - with organic hydrocarbons. High morbidity rates in adolescents were found for endocrine disorders, digestive system diseases, and musculoskeletal system disorders. Estimating the prevalence and incidence of newly diagnosed diseases among women in Aktau showed that the overall incidence rate, as well as the incidence of respiratory and skin diseases, declines with age. The incidence of the genitourinary system and the number of nervous disorders increase, and the number of neoplasms increases in men population. A study of carcinogenic risks showed that children with Aktau, especially boys, have the greatest risk of cancer. Conclusion: The conducted research shows that environmental factors have a big impact on the health of the population.